2016 ACC/AHA Guideline Focused Update on Duration of Dual Antiplatelet Therapy in Patients With Coronary Artery Disease: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines - Levine, Glenn N; Bates, Eric R; Bittl, John A; Brindis, Ralph G; Fihn, Stephan D; Fleisher, Lee A; Granger, Christopher B; Lange, Richard A; Mack, Michael J; Mauri, Laura; Mehran, Roxana; Mukherjee, Debabrata; et al. (Journal of the American College of Cardiology, 2016)
Each guideline is considered current unless and until it is updated, revised, or superseded by a published addendum.\n Munger Content Reviewer University of Utah--Professor of Pharmacy Practice None None None None None None E. Magnus Ohman Content Reviewer Duke University--Professor of Medicine, Director of Program for Advanced Coronary Disease AstraZeneca Janssen Pharmaceuticals[low *] None None Daiichi-Sankyo[low *] Eli Lilly[low *] Janssen Pharmaceuticals[low *] None None Eric R. Powers Content Reviewer Medical University of South Carolina--Service Line Medical Director None None None None None None Susan J. Pressler Content Reviewer--ACC/AHA Task Force on Clinical Practice Guidelines Indiana School of Nursing--Professor and Sally Reahard Chair; Center of Enhancing Quality of Life in Chronic Illness--Director None None None None None None Sunil V. Rao Content Reviewer Duke University Medical Center--Associate Professor of Medicine None None None None None None Philippe Gabriel Steg Content Reviewer Université Paris-Diderot--Professor AstraZeneca Bristol-Myers Squibb[low *] Daiichi-Sankyo Eli Lilly Merck None None AstraZeneca[low *] None None Tracy Y. Wang Content Reviewer Duke University Medical Center--Associate Professor of Medicine AstraZeneca[low *] Eli Lilly None None AstraZeneca[low *] Bristol-Myers Squibb[low *] Eli Lilly/Daiichi-Sankyo Alliance[low *] None None [black square] This table represents the relationships of reviewers with industry and other entities that were disclosed at the time of peer review and determined to be relevant to this document. Names are listed in alphabetical order within each category of review.According to the ACC/AHA, a person has a relevant relationship IF: a) the relationship or interest relates to the same or similar subject matter, intellectual property or asset, topic, or issue addressed in the document; or b) the company/entity (with whom the relationship exists) makes a drug, drug class, or device addressed in the document, or makes a competing drug or device addressed in the document; or c) the person or a member of the person's household has a reasonable potential for financial, professional or other personal gain or loss as a result of the issues/content addressed in the document.AATS indicates American Association for Thoracic Surgery; ACC, American College of Cardiology; ACEP, American College of Emergency Physicians; AHA, American Heart Association; CSL, Coordinated Science Laboratory; DSMB, data safety monitoring board; PCNA; Preventive Cardiovascular Nurses Association; SCA, Society of Cardiovascular Anesthesiologist; SCAI, Society for Cardiovascular Angiography and Interventions; STS, Society of Thoracic Surgeons; and SVM, Society for Vascular Medicine.